2012
DOI: 10.1002/cpa.21421
|View full text |Cite
|
Sign up to set email alerts
|

Corrigendum: Intersection homology with field coefficients: K‐Witt spaces and K‐Witt Bordism

Abstract: We construct geometric examples of pseudomanifolds that satisfy the Witt condition for intersection homology Poincaré duality with respect to certain fields but not others. We also compute the bordism theory of K-Witt spaces for an arbitrary field K, extending results of Siegel for K = Q.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
17
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
2
2
1

Relationship

2
3

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 15 publications
1
17
0
Order By: Relevance
“…To see that the bordism is via a Witt space, it is only necessary to observe that the link of the interior cone point in each such pinch bordism will be a wedge of S 2 s, and it is easy to compute that ImH 1 (∨ i S 2 ; K) = 0 for any K. But now, since all closed oriented 4 surfaces bound, Ω Z 2 −Witt 2 = 0. This special case was also over-looked in [1], though this argument holds for any field K and is consistent with the claim of [1] that Ω K−Witt 2 = 0 for all K. Thus we have shown that w : [1,Corollary 4.3] that the bordism groups depend only on the characteristic of the field, so for characteristic 2 it suffices to consider K = Z 2 .…”
supporting
confidence: 84%
See 4 more Smart Citations
“…To see that the bordism is via a Witt space, it is only necessary to observe that the link of the interior cone point in each such pinch bordism will be a wedge of S 2 s, and it is easy to compute that ImH 1 (∨ i S 2 ; K) = 0 for any K. But now, since all closed oriented 4 surfaces bound, Ω Z 2 −Witt 2 = 0. This special case was also over-looked in [1], though this argument holds for any field K and is consistent with the claim of [1] that Ω K−Witt 2 = 0 for all K. Thus we have shown that w : [1,Corollary 4.3] that the bordism groups depend only on the characteristic of the field, so for characteristic 2 it suffices to consider K = Z 2 .…”
supporting
confidence: 84%
“…Putting this together with the computations from [1] of Ω K−Witt * in dimension ≡ 4k + 2 mod 4 (which remain correct), we have the following theorem:…”
mentioning
confidence: 82%
See 3 more Smart Citations